Formation of lipid and polymer based gold nanohybrids using a nanoreactor approach1. Issue 91 (9th October 2015) - Witzigmann, Dominik; Sieber, Sandro; Porta, Fabiola; Grossen, Philip; Bieri, Andrej; Strelnikova, Natalja; Pfohl, Thomas; Prescianotto-Baschong, Cristina; Huwyler, Jörg
<x xml:space="preserve">Abstract</x> Nanocarriers encapsulating gold nanoparticles hold tremendous promise for biomedical applications. The nanoreactor approach offers a versatile, efficient, and highly reproducible preparation technology.